Cyber warfare techniques, tactics and tools for security practitioners - Andress, Jason (Syngress, 2011)
"Cyber Warfare explores the battlefields, participants and the tools and techniques used during today's digital conflicts."--Resource description page.
Includes bibliographical references and index. - Print version record
Keywords: Information warfare -- Handbooks, manuals, etc; Computer networks -- Handbooks, manuals, etc -- Security measures; Cyberspace -- Handbooks, manuals, etc -- Security measures; Guerre de l'information; Guides, manuels, etc; Réseaux d'ordinateurs; Sécurité; Mesures; Guides, manuels, etc; Cyberspace; Security measures; Computer networks; Security measures; Information warfare; Handbooks and manuals